PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUASAN KONSUMEN PADA TOKO BUNGA 3 PUTRA BARON NGANJUK - Solah, M.Safiq Ahlu (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The background of this research is due to the intense business competition, business people must have a strategy in defending their business. The purpose of this study was to determine the effect of product quality, price and promotion on purchasing decisions at a Toko Bunga 3 Putra. This study uses a causal causal technique with a sample of 40 respondents who were analyzed using the classical assumption test, multiple linear, coefficient of determination and hypothesis testing using SPSS version 25 software. the result that the three independent variables have a simultaneous effect on consumer satisfaction.